Pengaruh Sistem Pengendalian Manajemen Terhadap Peningkatan Performa Proses Kerja Dan Piutang Usaha Pada Perusahaan Pt. Astra International,Tbk-Tso (Studi Kasus Pada Pt Astra International Tbk-Tso Auto2000 Cab.Bogor) - Rahmat, Andy; Jasmadeti, Jasmadeti; Herawati, Heti (LPPM Institut Bisnis dan Informatika Kesatuan, 2019)
The purpose of this research is to learn and explain about the effect of management control system on the increasing of performance, working process and receivables. Management control system has significant impact in affecting company’s accomplishment and how it runs the productions ahead. It also covers management of receivables in determining credit policies, receivables turnover, and monitoring of receivables aging. Management control system contains supervising of human resources which undeniably important when running the production operational. Human resources give ideas and improvisations on upcoming issues faced by the company to achieve its targets and how it contributes to assist in problem solving. Based on the study, a conclusion can be made that management control system have significant impacts on supervision of human resources, monitoring activities, human resources performance measurements, performance evaluation, credit policies, receivables turnover and monitoring of receivables aging. The analysis uncovers the causes and obstacles that restricted company from achieving its goals. For instance, receivable turnover in 2014 had experienced a decline of 0.62% from previously 12.97% to 12.35% in 2015. Nonetheless, the average collection period can still be considered effective due to being collected before due date.